2
$\begingroup$

Consider the following function $$U(a,z)= \frac{1}{\Gamma(a)} \int^{\infty}_0 t^{a-1} \cdot (1+t)^{-a} e^{-zt} dt$$

My Try : Let $\tau= zt$, then : $$ U(a,z)= \frac{z^{-a}}{\Gamma(a)} \int^{\infty}_0 \tau^{a-1} \cdot (1+\frac{\tau}{z})^{-a} e^{-\tau} d\tau $$

So $$U(a,z) = \frac{z^{-a}}{\Gamma(a)} \lim_{R \to \infty} \int^{R}_0 \tau^{a-1} \cdot (1+\frac{\tau}{z})^{-a} e^{-\tau} d\tau $$ So for $|z| > R$, I can write the series expansion for $(1+\frac{\tau}{z})^{-a} = \displaystyle \sum^{\infty}_{n=0} c_n \frac{\tau^n}{z^n}$ where $c_n= (-1)^{n}\frac{a\cdot (a+1) \cdots (a+n-1)}{n!}$. So $$U(a,z) = \frac{z^{-a}}{\Gamma(a)} \lim_{R \to \infty} \int^{R}_0 \cdot \displaystyle \sum^{\infty}_{n=0} c_n \frac{\tau^{n+a-1}}{z^n} e^{-\tau} d\tau $$ Now, Can I exchange the integral (with the limit ?! ) and the infinite series ? If I can, then $$U(a,z) = \frac{z^{-a}}{\Gamma(a)} \cdot \displaystyle \sum^{\infty}_{n=0} c_n \frac{1}{z^n} \lim_{R \to \infty} \int^{R}_0 \tau^{n+a-1} e^{-\tau} d\tau = \frac{z^{-a}}{\Gamma(a)} \cdot \displaystyle \sum^{\infty}_{n=0} c_n \frac{\Gamma(n+a)}{z^n} $$ So I obtain the result mentioned in this wikipedia article http://en.wikipedia.org/wiki/Confluent_hypergeometric_function#Asymptotic_behavior

But I seriously doubt that I can exchange limit of the integral with the infinite series. I already appreciate any help, thanks !

$\endgroup$
  • 2
    $\begingroup$ The rigorous way to do this would be by using Watson's Lemma, which, in the end, says that the interchange $\lim_{R \to \infty} \sum_{n=0}^\infty = \sum_{n=0}^\infty \lim_{R \to \infty}$ holds as long as the resulting series is interpreted as an asymptotic series, valid for $z \to \infty$. $\endgroup$ – Antonio Vargas Mar 31 '15 at 20:05
2
$\begingroup$

The rigorous way to do this would be by using Watson's Lemma, which, in the end, says that the interchange $\lim_{R \to \infty} \sum_{n=0}^\infty = \sum_{n=0}^\infty \lim_{R \to \infty}$ holds as long as the resulting series is interpreted as an asymptotic series, valid for $z \to \infty$.

$\endgroup$
  • $\begingroup$ (Converted my comment to an answer so that this question will no longer show up in the unanswered queue.) $\endgroup$ – Antonio Vargas Mar 31 '15 at 21:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.